2022
DOI: 10.3748/wjg.v28.i26.3201
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular alpha-fetoprotein mitigates hepatocyte apoptosis and necroptosis by inhibiting endoplasmic reticulum stress

Abstract: BACKGROUND Endoplasmic reticulum (ER) stress contributes to the pathogenesis of chronic liver diseases, but how hepatocytes respond to ER stress has not been clarified. Alpha-fetoprotein (AFP) is secreted by hepatoma cells and elevated levels of serum AFP are associated with development of liver malignancies. AIM To investigate whether and how AFP could regulate ER stress and hepatocyte injury. METHODS The distribution of AFP and the degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In this study, CS treatment remarkably inhibited UUO-induced apoptosis and necroptosis, as evidenced by a decrease in the number of TUNEL-positive cells and the expression of key factors related to apoptosis (cleaved caspase-3, cleaved PARP-1, p53 and Bax) and necroptosis (RIPK1, RIPK3 and MLKL). Because both types of cell death can be induced by ER stress [ 84 , 85 ], the interplay between oxidative stress and ER stress can cause or exacerbate tubular cell apoptosis and necroptosis in UUO mice. Therefore, suppression of oxidative stress induced by CS may inhibit apoptosis and necroptosis through inhibiting UPR pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, CS treatment remarkably inhibited UUO-induced apoptosis and necroptosis, as evidenced by a decrease in the number of TUNEL-positive cells and the expression of key factors related to apoptosis (cleaved caspase-3, cleaved PARP-1, p53 and Bax) and necroptosis (RIPK1, RIPK3 and MLKL). Because both types of cell death can be induced by ER stress [ 84 , 85 ], the interplay between oxidative stress and ER stress can cause or exacerbate tubular cell apoptosis and necroptosis in UUO mice. Therefore, suppression of oxidative stress induced by CS may inhibit apoptosis and necroptosis through inhibiting UPR pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It regulates ER stress response by regulating the expression of different downstream target signals, promoting the homeostasis of the cell microenvironment and affecting necroptosis. In our study, ATF6 alleviated necroptosis through upregulating AFP in liver injury ( 70 ). However, it also upregulated RIP3 expression, which did not alleviate necroptosis of liver cells ( 69 ).…”
Section: Discussionmentioning
confidence: 56%
“…In contrast, IL-6/gp130 signaling may aggravate liver damage in autoimmune hepatitis (59). (70). However, it also upregulated RIP3 expression, which did not alleviate necroptosis of liver cells (69).…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the research by Schiavon et al [ 59 ] has indicated that UCB activates the nuclear factor kappa-B (NF-κB) pathway in vitro , leading to the mediation of inflammatory responses. Our preliminary research found that ER stress activates the apoptosis and necroptosis of liver cells in the setting of acute liver injury[ 60 , 61 ]. In vitro studies have revealed that UCB intervention increases the apoptosis and necroptosis of oligodendrocyte precursor cells[ 58 ].…”
Section: Discussionmentioning
confidence: 99%